5.1.5 Problems 401 to 500

Table 5.9: First order ode

#

ODE

Mathematica

Maple

1144

\[ {}y^{\prime } = \frac {x \left (x^{2}+1\right )}{4 y^{3}} \]

1145

\[ {}y^{\prime } = \frac {-{\mathrm e}^{x}+3 x^{2}}{-5+2 y} \]

1146

\[ {}y^{\prime } = \frac {{\mathrm e}^{-x}-{\mathrm e}^{x}}{3+4 y} \]

1147

\[ {}\sin \left (2 x \right )+\cos \left (3 y\right ) y^{\prime } = 0 \]

1148

\[ {}\sqrt {-x^{2}+1}\, y^{2} y^{\prime } = \arcsin \left (x \right ) \]

1149

\[ {}y^{\prime } = \frac {3 x^{2}+1}{-6 y+3 y^{2}} \]

1150

\[ {}y^{\prime } = \frac {3 x^{2}}{-4+3 y^{2}} \]

1151

\[ {}y^{\prime } = 2 y^{2}+x y^{2} \]

1152

\[ {}y^{\prime } = \frac {2-{\mathrm e}^{x}}{3+2 y} \]

1153

\[ {}y^{\prime } = \frac {2 \cos \left (2 x \right )}{3+2 y} \]

1154

\[ {}y^{\prime } = 2 \left (1+x \right ) \left (1+y^{2}\right ) \]

1155

\[ {}y^{\prime } = \frac {t \left (4-y\right ) y}{3} \]

1156

\[ {}y^{\prime } = \frac {t y \left (4-y\right )}{t +1} \]

1157

\[ {}y^{\prime } = \frac {a y+b}{d +c y} \]

1158

\[ {}y^{\prime } = \frac {y^{2}+x y+x^{2}}{x^{2}} \]

1159

\[ {}y^{\prime } = \frac {x^{2}+3 y^{2}}{2 x y} \]

1160

\[ {}y^{\prime } = \frac {4 y-3 x}{2 x -y} \]

1161

\[ {}y^{\prime } = -\frac {4 x +3 y}{y+2 x} \]

1162

\[ {}y^{\prime } = \frac {3 y+x}{x -y} \]

1163

\[ {}x^{2}+3 x y+y^{2}-x^{2} y^{\prime } = 0 \]

1164

\[ {}y^{\prime } = \frac {x^{2}-3 y^{2}}{2 x y} \]

1165

\[ {}y^{\prime } = \frac {3 y^{2}-x^{2}}{2 x y} \]

1166

\[ {}y \ln \left (t \right )+\left (t -3\right ) y^{\prime } = 2 t \]

1167

\[ {}y+\left (t -4\right ) t y^{\prime } = 0 \]

1168

\[ {}\tan \left (t \right ) y+y^{\prime } = \sin \left (t \right ) \]

1169

\[ {}2 t y+\left (-t^{2}+4\right ) y^{\prime } = 3 t^{2} \]

1170

\[ {}2 t y+\left (-t^{2}+4\right ) y^{\prime } = 3 t^{2} \]

1171

\[ {}y+\ln \left (t \right ) y^{\prime } = \cot \left (t \right ) \]

1172

\[ {}y^{\prime } = \frac {t^{2}+1}{3 y-y^{2}} \]

1173

\[ {}y^{\prime } = \frac {\cot \left (t \right ) y}{y+1} \]

1174

\[ {}y^{\prime } = -\frac {4 t}{y} \]

1175

\[ {}y^{\prime } = 2 t y^{2} \]

1176

\[ {}y^{3}+y^{\prime } = 0 \]

1177

\[ {}y^{\prime } = \frac {t^{2}}{\left (t^{3}+1\right ) y} \]

1178

\[ {}y^{\prime } = t \left (3-y\right ) y \]

1179

\[ {}y^{\prime } = y \left (3-t y\right ) \]

1180

\[ {}y^{\prime } = -y \left (3-t y\right ) \]

1181

\[ {}y^{\prime } = t -1-y^{2} \]

1182

\[ {}y^{\prime } = a y+b y^{2} \]

1183

\[ {}y^{\prime } = y \left (-2+y\right ) \left (-1+y\right ) \]

1184

\[ {}y^{\prime } = -1+{\mathrm e}^{y} \]

1185

\[ {}y^{\prime } = -1+{\mathrm e}^{-y} \]

1186

\[ {}y^{\prime } = -\frac {2 \arctan \left (y\right )}{1+y^{2}} \]

1187

\[ {}y^{\prime } = -k \left (-1+y\right )^{2} \]

1188

\[ {}y^{\prime } = y^{2} \left (y^{2}-1\right ) \]

1189

\[ {}y^{\prime } = y \left (1-y^{2}\right ) \]

1190

\[ {}y^{\prime } = -b \sqrt {y}+a y \]

1191

\[ {}y^{\prime } = y^{2} \left (4-y^{2}\right ) \]

1192

\[ {}y^{\prime } = \left (1-y\right )^{2} y^{2} \]

1193

\[ {}3+2 x +\left (-2+2 y\right ) y^{\prime } = 0 \]

1194

\[ {}2 x +4 y+\left (2 x -2 y\right ) y^{\prime } = 0 \]

1195

\[ {}2+3 x^{2}-2 x y+\left (3-x^{2}+6 y^{2}\right ) y^{\prime } = 0 \]

1196

\[ {}2 y+2 x y^{2}+\left (2 x +2 x^{2} y\right ) y^{\prime } = 0 \]

1197

\[ {}y^{\prime } = \frac {-a x -b y}{b x +c y} \]

1198

\[ {}y^{\prime } = \frac {-a x +b y}{b x -c y} \]

1199

\[ {}{\mathrm e}^{x} \sin \left (y\right )-2 y \sin \left (x \right )+\left (2 \cos \left (x \right )+{\mathrm e}^{x} \cos \left (y\right )\right ) y^{\prime } = 0 \]

1200

\[ {}{\mathrm e}^{x} \sin \left (y\right )+3 y-\left (3 x -{\mathrm e}^{x} \sin \left (y\right )\right ) y^{\prime } = 0 \]

1201

\[ {}2 x -2 \,{\mathrm e}^{x y} \sin \left (2 x \right )+{\mathrm e}^{x y} \cos \left (2 x \right ) y+\left (-3+{\mathrm e}^{x y} x \cos \left (2 x \right )\right ) y^{\prime } = 0 \]

1202

\[ {}\frac {y}{x}+6 x +\left (\ln \left (x \right )-2\right ) y^{\prime } = 0 \]

1203

\[ {}x \ln \left (x \right )+x y+\left (y \ln \left (x \right )+x y\right ) y^{\prime } = 0 \]

1204

\[ {}\frac {x}{\left (x^{2}+y^{2}\right )^{{3}/{2}}}+\frac {y y^{\prime }}{\left (x^{2}+y^{2}\right )^{{3}/{2}}} = 0 \]

1205

\[ {}2 x -y+\left (-x +2 y\right ) y^{\prime } = 0 \]

1206

\[ {}-1+9 x^{2}+y+\left (-4 y+x \right ) y^{\prime } = 0 \]

1207

\[ {}x^{2} y^{3}+x \left (1+y^{2}\right ) y^{\prime } = 0 \]

1208

\[ {}y+\left (2 x -{\mathrm e}^{y} y\right ) y^{\prime } = 0 \]

1209

\[ {}\left (x +2\right ) \sin \left (y\right )+x \cos \left (y\right ) y^{\prime } = 0 \]

1210

\[ {}2 x y+3 x^{2} y+y^{3}+\left (x^{2}+y^{2}\right ) y^{\prime } = 0 \]

1211

\[ {}y^{\prime } = -1+{\mathrm e}^{2 x}+y \]

1212

\[ {}1+\left (-\sin \left (y\right )+\frac {x}{y}\right ) y^{\prime } = 0 \]

1213

\[ {}y+\left (-{\mathrm e}^{-2 y}+2 x y\right ) y^{\prime } = 0 \]

1214

\[ {}{\mathrm e}^{x}+\left ({\mathrm e}^{x} \cot \left (y\right )+2 \csc \left (y\right ) y\right ) y^{\prime } = 0 \]

1215

\[ {}\frac {4 x^{3}}{y^{2}}+\frac {3}{y}+\left (\frac {3 x}{y^{2}}+4 y\right ) y^{\prime } = 0 \]

1216

\[ {}3 x +\frac {6}{y}+\left (\frac {x^{2}}{y}+\frac {3 y}{x}\right ) y^{\prime } = 0 \]

1217

\[ {}3 x y+y^{2}+\left (x y+x^{2}\right ) y^{\prime } = 0 \]

1218

\[ {}y^{\prime } = \frac {x^{3}-2 y}{x} \]

1219

\[ {}y^{\prime } = \frac {1+\cos \left (x \right )}{2-\sin \left (y\right )} \]

1220

\[ {}y^{\prime } = \frac {y+2 x}{3-x +3 y^{2}} \]

1221

\[ {}y^{\prime } = 3-6 x +y-2 x y \]

1222

\[ {}y^{\prime } = \frac {-1-2 x y-y^{2}}{x^{2}+2 x y} \]

1223

\[ {}x y+x y^{\prime } = 1-y \]

1224

\[ {}y^{\prime } = \frac {4 x^{3}+1}{y \left (2+3 y\right )} \]

1225

\[ {}x y^{\prime }+2 y = \frac {\sin \left (x \right )}{x} \]

1226

\[ {}y^{\prime } = \frac {-1-2 x y}{x^{2}+2 y} \]

1227

\[ {}\frac {-x^{2}+x +1}{x^{2}}+\frac {y y^{\prime }}{y-2} = 0 \]

1228

\[ {}x^{2}+y+\left ({\mathrm e}^{y}+x \right ) y^{\prime } = 0 \]

1229

\[ {}y^{\prime }+y = \frac {1}{1+{\mathrm e}^{x}} \]

1230

\[ {}y^{\prime } = 1+2 x +y^{2}+2 x y^{2} \]

1231

\[ {}x +y+\left (x +2 y\right ) y^{\prime } = 0 \]

1232

\[ {}\left (1+{\mathrm e}^{x}\right ) y^{\prime } = y-y \,{\mathrm e}^{x} \]

1233

\[ {}y^{\prime } = \frac {-{\mathrm e}^{2 y} \cos \left (x \right )+\cos \left (y\right ) {\mathrm e}^{-x}}{2 \,{\mathrm e}^{2 y} \sin \left (x \right )-\sin \left (y\right ) {\mathrm e}^{-x}} \]

1234

\[ {}y^{\prime } = {\mathrm e}^{2 x}+3 y \]

1235

\[ {}2 y+y^{\prime } = {\mathrm e}^{-x^{2}-2 x} \]

1236

\[ {}y^{\prime } = \frac {3 x^{2}-2 y-y^{3}}{2 x +3 x y^{2}} \]

1237

\[ {}y^{\prime } = {\mathrm e}^{x +y} \]

1238

\[ {}\frac {-4+6 x y+2 y^{2}}{3 x^{2}+4 x y+3 y^{2}}+y^{\prime } = 0 \]

1239

\[ {}y^{\prime } = \frac {x^{2}-1}{1+y^{2}} \]

1240

\[ {}\left (t +1\right ) y+t y^{\prime } = {\mathrm e}^{2 t} \]

1241

\[ {}2 \cos \left (x \right ) \sin \left (x \right ) \sin \left (y\right )+\cos \left (y\right ) \sin \left (x \right )^{2} y^{\prime } = 0 \]

1242

\[ {}\frac {2 x}{y}-\frac {y}{x^{2}+y^{2}}+\left (-\frac {x^{2}}{y^{2}}+\frac {x}{x^{2}+y^{2}}\right ) y^{\prime } = 0 \]

1243

\[ {}x y^{\prime } = {\mathrm e}^{\frac {y}{x}} x +y \]